2018
DOI: 10.1002/jper.18-0037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lozenges containing egg yolk antibody against Porphyromonas gingivalis gingipains as an adjunct to conventional non‐surgical therapy in periodontitis patients: A randomized controlled clinical trial

Abstract: The adjunctive use of lozenges containing IgY antibody against gingipains from P. gingivalis resulted in clinical and microbiological benefits in the treatment for chronic periodontitis. Additional investigations are needed to examine if the IgY brings benefits to case patients who do not receive SRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Also, treatment with IgY from hens immunized with whole F. nucleatum cells results in a marked decrease in alveolar bone loss after F. nucleatum infection in a mouse model [ 36 ]. A randomized controlled clinical trial of 64 patients with periodontitis showed that the adjunctive use of lozenges containing IgY against P. gingivalis gingipains results in reduction of gingival bleeding index and P. gingivalis cell in gingival pockets [ 37 ]. Further in vivo studies are needed to directly demonstrate the therapeutic effects of our two-in-one IgY.…”
Section: Discussionmentioning
confidence: 99%
“…Also, treatment with IgY from hens immunized with whole F. nucleatum cells results in a marked decrease in alveolar bone loss after F. nucleatum infection in a mouse model [ 36 ]. A randomized controlled clinical trial of 64 patients with periodontitis showed that the adjunctive use of lozenges containing IgY against P. gingivalis gingipains results in reduction of gingival bleeding index and P. gingivalis cell in gingival pockets [ 37 ]. Further in vivo studies are needed to directly demonstrate the therapeutic effects of our two-in-one IgY.…”
Section: Discussionmentioning
confidence: 99%
“…Additional clinical studies showing favorable safety of IgY given orally include treatment with a gel containing anti-Candida IgY ( 316 ), treatment with lozenges containing anti- P. gingivalis IgY ( 317 ), ingestion of anti-rotavirus IgY in pediatric patients with rotavirus diarrhea ( 63 , 67 ), and ingesting yogurt containing anti- H. pylori IgY ( 167 ). Parenteral administration of IgY has not been evaluated but may be of value as a single injection in situations such as the need for antivenom treatment.…”
Section: Principles Regarding the Clinical Use Of Igymentioning
confidence: 99%
“…An interesting option is the adjunctive use of lozenges containing IgY antibody against gingipains from P. gingivalis. It was shown that the use of this therapy resulted in clinical and microbiological benefits in the treatment for chronic periodontitis [252] and may actually also have therapeutic effects in PD.…”
Section: Additional Therapeutic Optionsmentioning
confidence: 99%